Facing the Mountain : Kibbutz as one - A Jewish-Arab Project - Environmental Sculpture. - Tamir, Tali; Grosman, Avishai; Art Focus Contemporary Israeli Art, Jerusalem 1994 (Israel : Givat Haviva, 1994)
Rabinovich, Noam ; Grinblat, Yoram ; Yerushalmi, Paula ; Bauman, tuli & Hater, Hasan ; Churi, Nida'a & Glotman, Joshua ; Brown, Ayala ; Serper, Tzuky ; Biberman, Efrat ; Chai, Galia ; Wallach, Ami ; Rubin, Yadid ; Herman, Ya'al ; Sha'altiel, Ohad ; Kotzer, Tzur ; Raz, Guy ; Domini, Drora ; etc.
Facing the Mountain : Kibbutz as one - A Jewish-Arab Project - Environmental Sculpture, Givat Haviva, 1994. Art Focus Contemporary Israeli Art, Jerusalem 1994
boek